Overconfidence versus Herd Mentality Bias: An Investment Decision - V, Sridevi; Saha, Sucharita; Ghosh, Risha; Ghosh, Risha; Misra, Siddharth (International Journal of Psychosocial Rehabilitation, 2019)
The research is based on the impact of overconfidence bias and herd mentality bias on investment decision-making and which one out of these has a significant influence on the investment decision. Primary data was collected with the help of a questionnaire using a random sampling method from a sample of 160 respondents consisting of investors belonging to different income levels and working sectors to work on this research. The finding of this research is that herd mentality bias is the one that affects the investment decision the most, and the favourable investment avenue is the stock market. The test was done with the help of regression analysis to find out the relationship between both overconfidence and herd mentality with each of the investment avenues, and the results were shown in a regression table. This was followed by a Johansen's co-integration test and descriptive analysis to find out whether both the biases are affecting the investors and which is the one that is affecting the most. From the regression analysis, it was also found out which is the most preferred investment area. From this piece of work, the investors can get a brief idea about their bias levels and how it is affecting their investment choices.